Fatal Haemorrhagic Stroke Due to Concomitant Abuse of Sildenafil and Alcohol: A Case Report - Jithin Laxminarayana V; Azmath Tabassum; Kapil D; Nagamohan Rao B V; Kattamreddy Ananth Rupesh (National Board of Examinations Journal of Medical Sciences)
Sildenafil is increasingly being abused recreationally for improving sexual endurance. The combined use of sildenafil with alcohol increases the risk of cerebrovascular accidents. We present the case of a 39-year-old male with no significant medical history who suffered a fatal stroke after consuming high doses of sildenafil while intoxicated with alcohol. Notable findings at autopsy include left ventricular hypertrophy, left capsuloganglioninc bleed and atherosclerotic changes in the coronary arteries. This case report highlights the risks of recreational sildenafil use, especially when combined with alcohol, and underscores the need for pharmacovigilance and public awareness.